Immunological comparison of scrapie-associated fibrils isolated from animals infected with four different scrapie strains. - Kascsak, R J (1986)
Scrapie-associated fibrils (SAFs) are abnormal filamentous structures that are uniquely associated with unconventional slow virus diseases. The antigenic relationships of SAFs from animals infected with four biologically distinct scrapie strains were investigated by using antisera raised to purified SAF proteins. Rabbit antisera were raised to SAFs isolated from mice infected with the ME7 scrapie strain and to SAFs isolated from hamsters infected with the 263K scrapie strain. A strong antigenic relationship was shown among SAF proteins (PrPs) isolated from all scrapie-infected animals (ME7, 139A, and 87V in mice and 263K in hamsters), and this relationship was demonstrable regardless of which antiserum was used. SAF proteins were antigenically distinct from those of paired helical filaments or amyloid isolated from patients with Alzheimer disease. Distinct Western blot profiles were demonstrated for SAFs isolated from animals infected with each scrapie strain. Differences seen among SAFs were independent, at least in part, of host species or genotype, implying that certain specific structural and molecular properties of SAFs are mediated by the strain of scrapie agent.